Fungi Contribute Critical but Spatially Varying Roles in Nitrogen and Carbon Cycling in Acid Mine Drainage - Mosier, Annika C.; Miller, Christopher S.; Frischkorn, Kyle R.; Ohm, Robin A.; Li, Zhou; LaButti, Kurt; Lapidus, Alla; Lipzen, Anna; Chen, Cindy; Johnson, Jenifer; Lindquist, Erika A.; Pan, Chongle; et al. (Frontiers in Microbiology, 2016)
The ecosystem roles of fungi have been extensively studied by targeting one organism and/or biological process at a time, but the full metabolic potential of fungi has rarely been captured in an environmental context. We hypothesized that fungal genome sequences could be assembled directly from the environment using metagenomics and that transcriptomics and proteomics could simultaneously reveal metabolic differentiation across habitats. We reconstructed the near-complete 27 Mbp genome of a filamentous fungus, Acidomyces richmondensis, and evaluated transcript and protein expression in floating and streamer biofilms from an acid mine drainage (AMD) system. A. richmondensis transcripts involved in denitrification and in the degradation of complex carbon sources (including cellulose) were up-regulated in floating biofilms, whereas central carbon metabolism and stress-related transcripts were significantly up-regulated in streamer biofilms. These findings suggest that the biofilm niches are distinguished by distinct carbon and nitrogen resource utilization, oxygen availability, and environmental challenges. An isolated A. richmondensis strain from this environment was used to validate the metagenomics-derived genome and confirm nitrous oxide production at pH 1. Overall, our analyses defined mechanisms of fungal adaptation and identified a functional shift related to different roles in carbon and nitrogen turnover for the same species of fungi growing in closely located but distinct biofilm niches.